2022
DOI: 10.1175/jcli-d-22-0124.1
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Anthropogenic Aerosol Forcing in the 1850–1985 Strengthening of the AMOC in CMIP6 Historical Simulations

Abstract: Previous work has shown that anthropogenic aerosol (AA) forcing drives a strengthening in the Atlantic Meridional Overturning Circulation (AMOC) in CMIP6 historical simulations over 1850–1985, but the mechanisms have not been fully understood. Across CMIP6 models, it is shown that there is a strong correlation between surface heat loss over the subpolar North Atlantic (SPNA) and the forced strengthening of the AMOC. Despite the link to AA forcing, the AMOC response is not strongly related to the contribution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(52 citation statements)
references
References 67 publications
(50 reference statements)
9
43
0
Order By: Relevance
“…Following this, ocean circulation is far from constant on timescales longer than a century or so. Indeed consideration of the Gulf Stream which keeps northern Europe warmer than other similar-latitude locations make it clear that changes to ocean circulation could potentially have enormous repercussions [8]. All of this is without any discussion at all of the longer-term implications gleaned from paleoclimate studies, e.g.…”
Section: Feedbacksmentioning
confidence: 99%
“…Following this, ocean circulation is far from constant on timescales longer than a century or so. Indeed consideration of the Gulf Stream which keeps northern Europe warmer than other similar-latitude locations make it clear that changes to ocean circulation could potentially have enormous repercussions [8]. All of this is without any discussion at all of the longer-term implications gleaned from paleoclimate studies, e.g.…”
Section: Feedbacksmentioning
confidence: 99%
“…The question of how aerosols affect North Atlantic SSTs is still actively debated, and could include the role of both direct radiative adjustments local to the region, as well as more indirect impacts from upstream emissions (Booth et al, 2012;Robson et al, 2022). Here we will only consider the hypothesis put forth by Robson et al (2022), due to it being based on a large multimodel ensemble, unlike most other studies.…”
Section: The Role Of Sulphate Aerosolsmentioning
confidence: 99%
“…The question of how aerosols affect North Atlantic SSTs is still actively debated, and could include the role of both direct radiative adjustments local to the region, as well as more indirect impacts from upstream emissions (Booth et al, 2012;Robson et al, 2022). Here we will only consider the hypothesis put forth by Robson et al (2022), due to it being based on a large multimodel ensemble, unlike most other studies. In their study, they argued that sulphate aerosol emissions over the eastern part of North America led to a cooling of surface temperatures there, and that this cool air was then advected over the North Atlantic, thereby cooling the SSTs and ultimately modulating the AMOC.…”
Section: The Role Of Sulphate Aerosolsmentioning
confidence: 99%
“…Cooling would have the opposite effect, leading to increases in F SW in the North Atlantic region. It has also been suggested that aerosols may have a local influence on the Atlantic Meridional Overturning Circulation (AMOC) that is more direct than the effect of aerosols on large scale temperatures (Yu and Pritchard, 2019;Robson et al, 2022). Menary et al (2020) shows that the AMOC speeds up in the DAMIP-hist-aer run as a result of aerosol emissions and it is feasible that changes in the AMOC could also lead to changes in cloud cover or properties and hence changes in F SW .…”
Section: Aerosol Forcing Vs Cloud-climate Feedbacksmentioning
confidence: 99%
“…Here we can only speculate about possible reasons for this; further work would be needed to draw conclusions. One possibility is that the dedicated aerosol-only DAMIP-hist-aer simulation allows the AMOC to increase in strength until 1970 due to the increase in aerosols over that period, which is a proven effect of aerosol forcing in many models (Menary et al, 2020;Robson et al, 2022). This may prevent a rapid response of the climate in the NA to the post-1970 reduction in aerosols due to inertia in the AMOC perhaps related to ocean heat storage, sea-ice changes, etc.…”
Section: A6 Summarymentioning
confidence: 99%